Physical Performance Prediction Using Anthropometric Measurements as Indicators In Futsal Players - Jejo , Stevan (Journal of Physical Education, 2019)
The research aims at identifying the relationship between anthropometric measurements with some physical fitness components in futsal players aged 10 – 12 years old as well as identifying the contribution of anthropometric measurements in some physical fitness components futsal players aged 10 – 12 years old. It also aims at identifying the proficiency of some anthropometric measurements in predicting some physical fitness components in futsal players aged 10 – 12 years old. The subjects were (25) futsal players from Qaraqoosh sport club for male players aged 10 – 12 years old. The results of the study show (10) weak correlation with physical fitness components, moderate contribution with anthropometric measurements and great contribution in leg calf in explosive power and force – speed for legs. The researcher came up with a general prediction formula from physical fitness components and anthropometric measurements.